Effect of hybrid doping on dielectric behavior of barium titanate ceramics. Issue 175 (12th October 2016) - Sareein, Thanapong; Albutt, Naphat; Unruan, Muanjai; Funsueb, Narit; Ngamjarurojana, Athipong; Yimnirun, Rattikorn
ABSTRACT: Hybrid-doped BaTiO3 ferroelectric polycrystalline ceramic samples were synthesized by solid state reaction. The concentration of La 3+ was fixed 1 mol% while that of Sm 3+ varied from 1 to 4 mol%. The effect of the replacement, which can be either lanthanum or samarium, in a cationic site on structural and physical properties of BaTiO3 was investigated. The dielectric permittivity changed significantly with temperature in a wide temperature rang. It was found that the dielectric behavior can be ascribed to the change in defect concentrations in different lattice locations in BaTiO3 structure.